Acoustic Signal Monitoring System for Submerged Environments - Ahmad Zarkasi; Khafidawati Saputri Sabir; Kholis Nurhanafi; Syahrir Syahrir; Mislan Mislan; Rahmawati Munir; Auliya Rahmatul Ummah (Tinta Emas Publisher, 2026)
Passive acoustic monitoring offers a non-invasive means of detecting biological, geophysical, and anthropogenic sound sources in aquatic environments, but the cost and availability of commercial recorders can limit field use. This study developed a portable, low-cost acoustic recorder comprising a waterproofed condenser microphone, a pre-amplifier, and an adjustable high-pass filter, and evaluated it against a Dolphinear DE200 reference instrument. Preliminary frequency-linearity tests produced coefficients of determination of 0.99978 for the reference instrument and 0.99981 for the proposed instrument. Airborne tests were conducted from 200 Hz to 20 kHz, followed by underwater tests at nominal source frequencies of 1, 2, 5, 10, 15, and 20 kHz. Both instruments localized the principal spectral peaks close to the imposed frequencies. Activating the filter suppressed low-frequency components, including the 200 Hz airborne tone, while signals from 500 Hz to 20 kHz remained detectable. Underwater measurements showed source-related peaks near 0.991, 1.981-2.024, 4.996, 9.991, 14.987, and 19.983 kHz; however, the 20 kHz condition approached the upper edge of the acquisition band and should be interpreted cautiously. Because the prototype sensor chain was not pressure-calibrated, the amplitude spectra represent relative intensity rather than absolute sound pressure level. The prototype therefore provides a promising proof of concept for affordable audible-band underwater detection and educational or exploratory monitoring, while quantitative environmental deployment will require hydrophone calibration, replicated signal-to-noise measurements, and validation under controlled geometry.